2021
DOI: 10.1093/infdis/jiab411
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Dynamics of SARS-CoV-2 Infection in a Diverse Population: 6-Month Evaluation of a Prospective Cohort Study

Abstract: Background We studied risk factors, antibody responses, and symptoms of SARS-CoV-2 infection in a diverse, ambulatory population. Methods A prospective cohort (n=831, including 548 hospital-based healthcare workers) previously undiagnosed with SARS-CoV-2 infection was followed for six months with serial testing (SARS-CoV-2 PCR, specific IgG) and surveys. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 45 publications
6
22
1
Order By: Relevance
“…From 50 individuals who agreed to participate in the first testing, 45 had a positive RT-PCR result during the outbreak and 34 of them self-reported either asymptomatic or very mild or mild infection, while 11 self-reported moderate to severe COVID-19. The seropositivity rate after an asymptomatic SARS-CoV-2 infection was lower when compared to symptomatic infection of different severity, which is in line with other studies [26]. Another issue addressed during the first serological testing was related to the persistence of virus-specific IgM and its potential diagnostic value for an acute SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…From 50 individuals who agreed to participate in the first testing, 45 had a positive RT-PCR result during the outbreak and 34 of them self-reported either asymptomatic or very mild or mild infection, while 11 self-reported moderate to severe COVID-19. The seropositivity rate after an asymptomatic SARS-CoV-2 infection was lower when compared to symptomatic infection of different severity, which is in line with other studies [26]. Another issue addressed during the first serological testing was related to the persistence of virus-specific IgM and its potential diagnostic value for an acute SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 86%
“…To date, both sero-epidemiological and targeted cohort studies from different countries have reported detectable levels of virus-specific antibodies and duration of the protective immune response from 3 to 13 months after infection [6,7,10,12,13,17,19,21,24,25]. Previous cohort studies on the formation and persistence of SARS-CoV-2-specific humoral immune response mainly included healthcare workers as a target group having the highest risk of being exposed to SARS-CoV-2 [13,14,16,19,20,24,26,27]. However, a long-term monitoring of antibody levels in naturally infected healthcare workers seems to be difficult or even impossible after the start of a global vaccination, as the healthcare sector is considered a priority group for vaccination in many countries [28].…”
Section: Discussionmentioning
confidence: 99%
“…We have not observed an association between BMI, obesity, regular exercise, or alcohol consumption and post-COVID-19 symptoms, in contrast with other studies [31,53]. In addition, high levels of anti-SARS-CoV-2 antibodies or their increase between June 2020 and October 2020 were not associated with complications, recovery, and return to the usual health [33], contrary to other studies [25,28,57]. However, attendance of MGEs, observing a person with a cough at MGEs, and contact with a COVID-19 patient were associated with complications, inferior recovery, and less frequent return to usual health.…”
Section: Discussioncontrasting
confidence: 99%
“…The frequency of complications subsequent to the acute phase has important variations in the ranges from 10% to 93% [3,5,8,[19][20][21][22][23][24][25]. The studies of post-COVID-19 complications are heterogeneous; including hospitalized versus non-hospitalized patients, with variable demographic characteristics of patients, the severity of the disease, follow-up time, different measures of the complications, control groups for comparison, designs, sample size, and statistical analysis [5,21,[26][27][28][29]. In this situation, accruing evidence on the frequency and the manifestation of LCS and related risk factors is needed [22,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…So far, the clues have been limited. A handful of studies have identified higher levels of binding or neutralizing antibodies in those with PASC, 122,123 suggesting that persistent symptoms could be a manifestation of more severe illness (which is known to be associated with higher antibody levels and correlated with higher risk of developing PASC) or possibly persistent immune stimulation. 14 Other studies have found that the humoral response appears lower among those with persistent symptoms.…”
Section: Cov-2 Infection (Pasc)mentioning
confidence: 99%